Do multiple stroke-related educational opportunities enhance stroke knowledge among students enrolled in communication sciences and disorders programs? - Lankford KS; Marshall EL; Pittman AD; Ellis C (Internet Journal of Allied Health Sciences & Practice, 2008)
Purpose: Stroke education modules have been added to medical school curriculums to improve stroke knowledge in graduate physicians, and this has resulted in positive outcomes. These findings suggest that similar strategies may be successful in graduate programs such as Communication Sciences and Disorders (CSD). The purpose of this study was to examine the impact of multiple stroke-related education opportunities on students enrolled in CSD programs. Methods: Seventy-six first and second year students enrolled in a Communication Sciences and Disorders program completed a survey of stroke risk factors and early warning signs of stroke. Results: Risk factor knowledge - 97% identified smoking as a risk factor; 61% identified diabetes; 90% identified high cholesterol; 84% identified age, and 90% identified physical inactivity. Students varied in their recognition of diabetes as a stroke risk factor based on their level of instruction. Early warning signs and first response knowledge - 83% recognized sudden confusion or trouble speaking; 100% recognized sudden facial, arm or leg weakness; 83% recognized sudden vision loss; 76% recognized sudden trouble walking; and 75% recognized sudden headache as early warning signs of stroke. Seventy-nine percent recognized calling 9-1-1 as the appropriate first action. Students varied in their recognition of sudden trouble walking and severe headache as an early warning sign of stroke based on their level of instruction. Conclusions: Most students recognized individual stroke risk factors and early warning signs, but few recognized multiple risk factors and warning signs. Multiple education opportunities appear to enhance student recognition of risk factors and warning signs.